2020
DOI: 10.1016/j.buildenv.2019.106559
|View full text |Cite
|
Sign up to set email alerts
|

Polyurethane insulation and household products – A systematic review of their impact on indoor environmental quality

Abstract: We systematically review the impact of polyurethane insulation and polyurethane household products on the indoor environmental quality of buildings. The review breaks down polyurethane products into constituent compounds (isocyanate, polyol, flame retardant, blowing agent and catalyst) as well as secondary emissions, and discusses their implications on human health. Concentrations of compounds emitted from insulation, and household materials, measured in laboratory experiments and case studies are presented in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(25 citation statements)
references
References 102 publications
(130 reference statements)
0
22
0
1
Order By: Relevance
“…Polyurethane is widely used in thermal insulation materials and household products [ 119 ], so the indoor air pollution caused by flame-retardant polyurethane has been paid attention to, especially as people spend most of their time indoors [ 120 ]. Additive flame retardants will not chemically bound to polyurethane products, so it is based on this to measure the concentration of flame retardants in indoor environment [ 119 ]. Recent studies have even reported the migration of flame retardants to artificial sweat through contact and dermal penetration (mediated by sweat) [ 121 ].…”
Section: Progress Of Flame-retardant Pumentioning
confidence: 99%
“…Polyurethane is widely used in thermal insulation materials and household products [ 119 ], so the indoor air pollution caused by flame-retardant polyurethane has been paid attention to, especially as people spend most of their time indoors [ 120 ]. Additive flame retardants will not chemically bound to polyurethane products, so it is based on this to measure the concentration of flame retardants in indoor environment [ 119 ]. Recent studies have even reported the migration of flame retardants to artificial sweat through contact and dermal penetration (mediated by sweat) [ 121 ].…”
Section: Progress Of Flame-retardant Pumentioning
confidence: 99%
“…Therefore, careful selection of materials can improve air quality, healthy, and comfortable indoor environments [64]. In this regard, previous research has been done for different parts of non-structural building materials including floor [65,66], wallpaper [67,68], insulation [69,70], adhesive [71], paint [72], and wood-based panels [73]. However, the current research focused on a specific biocomposite as GBM especially fabricated from non-toxic, natural, and organic materials that could reduce IAQ contaminants and the accompanying complaints and claims.…”
Section: Biocomposite As Gbms To Decline Voc Emissionsmentioning
confidence: 99%
“…Therefore, TPUs bear unique chemistry which gave them a wide variation in their physical and mechanical properties making them suitable for many fields like automotive interior, the outer case of electronic devices, or transparent films 5–7 . Moreover, segmented PUs elastomers became among the most useful biomaterials in the biomedical field 8–14 . For instance, they are employed in fabricating blood bags, heart valves, vascular grafts, long and short‐term implants, and cardiac pumps 15–20 .…”
Section: Introductionmentioning
confidence: 99%